A Seventeen Multilevel High-Power Application Inverter with Low Total Harmonic Distortion - Ajmal Farooq; Shanshan Tu; Fiaz Ahmad; Muhammad Zeeshan Malik; Obaid U. Rehman; Ghulam Hafeez; Sadaqat ur Rehman (International Journal of Photoenergy)
In this paper, a new topology of multilevel inverter (MLI) is designed with a fewer number of components and low total harmonic distortion (THD) for high-power photovoltaic (PV) systems. The key limitations of conventional MLI topologies are high total harmonic distortion (THD) and the use of a large number of switching components due to which the cost of the overall inverter is high. In conventional MLI, THD can be significantly reduced by the addition of a large value filter element at the input side; however, it will result in increased size and cost. Thus, achieving a pure sinusoidal AC at the output and to maintain a low THD level is a major issue in conventional MLIs. The proposed MLI has the advantage of decreasing the output THD by using a modified form of the cascaded H-Bridge structure and sine pulse width modulation technique. The proposed inverter consists of 6 unidirectional switches and 2 bidirectional switches, and there is no extra requirement for additional voltage balancing capacitors or clinching diodes. The individual switching states and SPWM operation for generating the gate pulses of the proposed MLI are discussed in detail. Relevant waveforms are plotted, equations are derived, and mathematical analysis is carried out. A steady-state analysis of the proposed MLI demonstrates an output voltage with 17 levels while using only four DC sources. Simulation results of the proposed MLI for single-phase and three-phase structures are obtained, and comparison is carried out with existing MLI topologies which shows that the proposed MLI has significantly low THD and better performance. From the results, it is clear that the proposed MLI has a THD of 3.52% in comparison with four conventional MLIs whose THDs are 6.1%, 6.63%, 7.3%, and 9.93%. Moreover, the proposed MLI generates 17 voltage levels by using only 08 switching devices, whereas the conventional MLIs use more than 10 switching devices for the generation of 15 voltage levels.